Apoptosis and clinical severity in patients with psoriasis and HCV infection - Sami A Gabr; Mohamed A Berika; Ahmad H Alghadir (Wolters Kluwer Medknow Publications, 2014)
Background: It has been proposed that hepatitis C virus (HCV) antigens are involved in the pathogenesis of psoriasis and may contribute to severity of the disease. Increased expression of the apoptosis-regulating proteins p53 and tTG and decreased levels of bcl-2 in the keratinocytes of the skin of psoriatic patients have been reported. Aim: This study aims to identify the serum levels of apoptosis-regulating proteins in patients with psoriasis and without HCV infection and to study the relation between clinical severity of psoriasis and the presence of HCV infection. Materials and Methods: Disease severity was assessed by psoriasis area severity index score (PASI) of 90 patients with psoriasis grouped as mild (n = 30), moderate (n = 30) and severe (n = 30); 20 healthy individuals were used as controls. All groups were subjected for complete history taking, clinical examination, and tests for liver function and HCV infection. The serum levels of apoptosis related proteins: p53, tTG and bcl-2 were estimated by enzyme linked immune sorbent assay (ELISA). Results: There was a statistically significant (P < 0.001) correlation between clinical severity of psoriasis and presence of HCV antibodies and HCV-mRNA. In addition, significantly (P < 0.001) raised serum p53 and tTG, and reduced bcl-2 were observed among HCV-positive patients as compared to HCV-negative patients and control patients. Conclusion: These results conclude that clinical severity of psoriasis is affected by the presence of HCV antibodies and overexpression of apoptotic related proteins. In addition, altered serum levels of apoptosis-regulating proteins could be useful prognostic markers and therapeutic targets of psoriatic disease.